A reference map of murine cardiac transcription factor chromatin occupancy identifies dynamic and conserved enhancers - Brynn N. Akerberg (Nature Portfolio, 2019)
Mapping transcription factors (TFs) occupancy is essential for understanding transcriptional programs. Here the authors use biotinylated knockin alleles of key cardiac TFs (GATA4, NKX2-5, MEF2A, MEF2C, SRF, TBX5, TEAD1) to map their genome-wide occupancy in the fetal and adult mouse heart, providing insight into the cardiac transcriptional regulatory network.